Analisis Framing Pemberitaan Pelecehan Seksual OlehRaja Keraton Kasunanan Surakarta Hadiningrat (PB XIII Hangabehi) Di Media Online (Analisis Framing Pemberitaan Pelecehan Seksual oleh Raja Kasunanan Surakarta di Situs solopos.com dan detik.com Periode 23-29 Bulan September 2014) - Puji Lestari, Rita, Drs. Joko Sutarso, S.E, M. Si (2017)
News about cases of sexual abuse allegedly committed by King Keraton Surakarta Pakubowono XIII Hangabehi widely reported in various media. The position of king in Surakarta make a scandal of sexual abuse of underage girls have become a source of important when lifting a news media because it would be interesting for the audience's attention and investigated. There are interesting things done by solopos.com and detik.com in preaching the issue that there are differences shown by both in presenting the news. The purpose of this study was to determine and describe the framing of the news presented by solopos.com and detik.com on cases of sexual abuse allegedly committed by King Keraton Surakarta Pakubowono Hangabehi XIII. Analysis framing is an art or creativity with the different conclusion, although the same case. Even with the construction of news to each other have different construction framing. By using the framing analysis of Robert Entman writer trying to get to know the results of news framing the research object. The results of this study indicate that in this study the media have a presumption in favor of one group. Some of the effects resulting media can not be neutral in reporting certain issues. Detik.com have a tendency in reporting the case of a sex scandal made by the King of Surakarta Palace Pakubowono Hangabehi XIII, King's position as highlighted in the selection of headlines on detik.com. whereas prioritize news solopos.com victims, about his case to the support of various parties to achieve the justice of the case.